ORGANIZATIONAL AND ECONOMIC ASPECTS OF FORMATION OF CLUSTERS IN THE MINING INDUSTRY IN UKRAINE - YATSYKOVSKYY, BOGDAN; IVANYSHYNA, GALYNA; HOLUBKA, STEPAN (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article substantiates that an effective method of ensuring sustainable development of mining entities, an effective type of cooperation, in the process of which individual entities combine efforts in a common system (from geological exploration, field development, production to the sale of certain mining products ), there is a cluster. The opportunities that appear in the business entities (members of the cluster association), the implementation of which will determine the effective results of each participant, the development of the mining industry and, accordingly, the national economy as a whole. The classification of clusters on various grounds is presented, and the need to clarify the understanding of "industry clusters" is argued. The functioning of branch clusters has been clarified both in relation to the members of the cluster association and in relation to the subject of activity of the branch cluster. The author's approach to understanding clusters according to the "sectoral" classification can unite participants from different regions of Ukraine (this is especially important for the mining industry), and the tasks of the sectoral cluster should be determined by appropriate criteria. The peculiarities of the development of cluster associations in different countries are highlighted. It is argued that the formation of a cluster in the mining industry must be based on existing experience of clusters in different countries and achieve all the benefits that can be achieved by joining forces. The organizational and economic mechanism of functioning and development of the mining industry cluster has been developed, which will be presented as a set of elements aimed at the development of cluster entities through the implementation of their strategies (including functional) within the overall conceptually agreed strategy and cluster development.
Keywords: mining industry; cluster; association; mechanism